2013
DOI: 10.1111/liv.12131
|View full text |Cite
|
Sign up to set email alerts
|

Screening for hepatitis B and C in first‐generation Egyptian migrants living in the Netherlands

Abstract: Anti-HCV and HBsAg prevalence among Egyptian migrants was lower compared with the general Egyptian population, but higher than the general population of Western countries. Phylogenetic analyses suggest that all infections were from the region of origin. HCV-screening programmes should target first-generation Egyptian migrants, especially those of older age and those who received PAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
0
35
1
Order By: Relevance
“…In Malta, where most migrants tested were from Somalia, only 31 out of 5000 were found HBsAg positive [20]. Among first generation migrants tested in the Netherlands, the prevalence of HBsAg was estimated to be 3.8%, [22] whereas it was 1.1% among Egyptians [27]; further studies found anti-HBc prevalence ranging from 16.8 to 20%, showing high variability in accordance with age groups and ethnicity [24]. Furthermore, prevalence of HBsAg positivity of 5.9% was found among migrants in Portugal [29].…”
Section: Hepatitis B Virusmentioning
confidence: 97%
“…In Malta, where most migrants tested were from Somalia, only 31 out of 5000 were found HBsAg positive [20]. Among first generation migrants tested in the Netherlands, the prevalence of HBsAg was estimated to be 3.8%, [22] whereas it was 1.1% among Egyptians [27]; further studies found anti-HBc prevalence ranging from 16.8 to 20%, showing high variability in accordance with age groups and ethnicity [24]. Furthermore, prevalence of HBsAg positivity of 5.9% was found among migrants in Portugal [29].…”
Section: Hepatitis B Virusmentioning
confidence: 97%
“…The virus shows evidence of continuous transmission in health care settings as well as within households [2]. Due to the absence of vaccines and drugs for post-exposure prophylaxis, precautionary measures preventing future spread is the cornerstone for prevention [3]. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, a potentially large number of infected individuals remain unidentified or are identified late [3]. A major barrier to seeking HCV treatment is unawareness of HCV seropositivity [4].…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence was expected based on previous estimations in these hotspots (0.5% to 1%), 27,28 or other Dutch studies focusing on risk groups (0.3% to 4.8%), 32,34,38,39 and on (inter)national estimations that a substantial population is untested. [2][3][4][5] Estimates of the hidden HCV-infected population, however, are largely derived from mathematical models (43% to 72%).…”
Section: Discussionmentioning
confidence: 51%